2013
DOI: 10.1080/14719037.2013.806573
|View full text |Cite
|
Sign up to set email alerts
|

Leader–Member Exchange and Relational Quality in a Singapore Public Sector Organization

Abstract: An objective of Singapore's ongoing public sector reform (PS21) requires agencies to focus on getting the best out of its employees. One way of doing this is by creating a positive leadermember exchange (LMX) relationship, enabling supervisors to motivate their subordinates towards the development of organizational citizenship behaviours (OCB). This paper reports the extent of LMX and relational quality in a public sector agency experiencing PS21 reform and high staff turnover. In addition, we examined the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 88 publications
1
20
2
Order By: Relevance
“…Although meta-analyses conducted by Organ and Ryan (1995) and Fassina, Jones, and Uggerslev (2008) showed a positive relationship between job satisfaction and OCB, and other studies (Bateman & Organ, 1983;1994;LePine et al, 2002;Morrison, 1994;Yoon & Suh, 2003) also confirmed job satisfaction as an independent predictor of OCB, the results of studies conducted in the public sector have not been so consistent. For example, while a positive association between job satisfaction and OCB was found in the studies conducted by Yeo et al (2013) and by Tang and Ibrahim (1998), the associations reported in studies conducted by Alotaibi (2001) and Kim (2006) were nonsignificant.…”
Section: Job Satisfaction Organizational Justice Task Interdependencontrasting
confidence: 50%
See 2 more Smart Citations
“…Although meta-analyses conducted by Organ and Ryan (1995) and Fassina, Jones, and Uggerslev (2008) showed a positive relationship between job satisfaction and OCB, and other studies (Bateman & Organ, 1983;1994;LePine et al, 2002;Morrison, 1994;Yoon & Suh, 2003) also confirmed job satisfaction as an independent predictor of OCB, the results of studies conducted in the public sector have not been so consistent. For example, while a positive association between job satisfaction and OCB was found in the studies conducted by Yeo et al (2013) and by Tang and Ibrahim (1998), the associations reported in studies conducted by Alotaibi (2001) and Kim (2006) were nonsignificant.…”
Section: Job Satisfaction Organizational Justice Task Interdependencontrasting
confidence: 50%
“…For example, while Tang and Ibrahim (1998) and Yeo et al (2013) reported a statistically significant relationship between job satisfaction and OCB, Kim (2006) did not find such a relationship in a sample of Korean civil servants. Moreover, results of other studies that have presented a statistically positive association between job satisfaction and OCB variables are inconclusive in that these findings were based primarily on bivariate correlation coefficients (Alotaibi, 2001;Noblet et al, 2006).…”
Section: The Question Is: What Factors Influence Government Employeescontrasting
confidence: 48%
See 1 more Smart Citation
“…Of note, not much research has been conducted on the possible differences between sectors in the working market (e.g., private, public, government). Most of the extant research has been concerned with investigating specific sectors, independently of each other (e.g., Kunze & Miller, 2017;Yeo, Ananthram, Teo, & Pearson, 2015) and scarcely have the different sector types been compared (but see Johnson, Leenders, & McCue, 2017;Top, Akdere, & Tarcan, 2015).…”
Section: Organization Typesmentioning
confidence: 99%
“…As such, there would be a strong relationship between trust and LMX. Yeo et al (2015) found that LMX mediates the relationship between organizational justice and OCB in a Singapore public sector organization. LMX was also positively correlated to job satisfaction.…”
Section: Leader-member Exchange (Lmx)mentioning
confidence: 99%